Exploring EFL pre-service teachers’ emotional geographies during teaching practicum: A qualitative case study from Southeast Sulawesi, Indonesia - Riski Riski; Zulfa Sakhiyya (Journal on English as a Foreign Language, 2025)
As a response to interaction with the school environment during teaching practice, emotional experiences in teaching are still a challenge for future English as a foreign language (EFL) teacher candidates. Despite the growing focus on emotional studies, there is a lack of exploration of EFL pre-service teachers' (PSTs) emotional geographies during teaching practicum. To address this gap, it is crucial to investigate PSTs’ emotional geographies in teaching practicum. Hence, this qualitative case study enlisted four EFL PSTs from one of the state Islamic institutes in Southeast Sulawesi who have completed teaching practice in two schools in Kendari, Indonesia. The data were collected through written reflection, interviews, and focus group discussions (FGD). Afterwards, data were analyzed following the thematic analysis (Braun & Clarke, 2006) using the framework of emotional geographies of teaching (Hargreaves, 2001). Results show that participants showed positive and negative emotions during their teaching practice in moral dimensions. Those emotions are implicated in developing their competencies, including professional and cognitive aspects. These emotions influence students' study and follow-through, fostering a positive attitude. The study emphasizes the importance of EFL pre-service teachers developing emotional awareness and building strong connections within schools to successfully address challenges during their teaching practices.